Integrated power and thermal management system in a parallel hybrid-electric aircraft: an exploration of passive and active cooling and temperature control - Ouyang, Zeyu; Nikolaidis, Theoklis; Jafari, Soheil; Pontika, Evangelia (MDPI, 2025)
Hybrid-electric aircraft (HEAs) represent a promising solution for reducing fuel consumption and emissions. However, the additional heat loads generated by the electrical propulsion systems in HEAs can diminish these benefits. To address this, an integrated power and thermal management system (IPTMS) is essential to mitigate these challenges by optimizing the interaction between thermal management and power management. This paper presents a preliminary IPTMS design for a parallel HEA operating under International Standard Atmosphere (ISA) conditions. The design includes an evaluation of active cooling, passive cooling, and active temperature control strategies. The IPTMS accounts for heat loads from the engine system, including the generators, shaft bearings, and power gearboxes, as well as from the electrical propulsion system, such as motors, batteries, converters, and the electric bus. This study investigates the impact of battery power (BP) contribution to cooling power on required coolant pump power and induced ram air drag. A comparison of IPTMS performance under 0% and 100% BP conditions revealed that the magnitude of battery power contribution to cooling power does not significantly impact the thermal management system (TMS) performance due to the large disparity between the total battery power (maximum 950 kW) and the required cooling power (maximum 443 W). Additionally, it was determined that the motor-inverter loop accounts for 95% of the pump power and 97% of the ram air drag. These findings suggest that IPTMS optimization should prioritize the thermal domain, particularly the motor-inverter loop. This study provides new insights into IPTMS design for HEAs, paving the way for further exploration of IPTMS performance under various operating conditions and refinement of cooling strategies.
Keywords: 40 Engineering; 4008 Electrical Engineering; 4001 Aerospace Engineering